2023
DOI: 10.1167/iovs.64.5.11
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Sequencing Analysis Identifies Cross-Cohort Gut Microbial Signatures Associated With Age-Related Macular Degeneration

Abstract: Purpose Alterations in the gut microbiota have been associated with age-related macular degeneration (AMD). However, the dysbiosis shared by different ethnicity and geographic groups, which may associate with the disease pathogenesis, remain underexplored. Here, we characterized dysbiosis of the gut microbiota in patients with AMD from Chinese and Swiss cohorts and identified cross-cohort signatures associated with AMD. Methods Shotgun metagenomic sequencing was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…For example, while Burri et al reported an increase in Negativicutes and a decrease in Oscillibacter in 57 AMD patients as compared to 58 healthy controls, Zhang et al showed that AMD subjects are enriched in the pro-inflammatory Escherichia-Shigella and depleted in the SCFA-producing Blautia and Anaerostipes [63,64]. Moreover, Xue et al identified Ruminococcus callidus and Lactobacillus gasseri (both belonging to the Firmicutes phylum) as the most significantly associated with AMD after combining data from two population cohorts (Chinese and Swiss) [65], while Zinkernagel et al showed an increase in Oscillibacter, Anaerotruncus, Eubacterium ventriosum, and Ruminococcus torques in AMD patients versus control subjects that, instead, presented a higher content of Bacteroides eggerthii [49]. Still, a reduced Firmicutes/Bacteroides ratio seems to characterize AMD across the different studies [63,65].…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, while Burri et al reported an increase in Negativicutes and a decrease in Oscillibacter in 57 AMD patients as compared to 58 healthy controls, Zhang et al showed that AMD subjects are enriched in the pro-inflammatory Escherichia-Shigella and depleted in the SCFA-producing Blautia and Anaerostipes [63,64]. Moreover, Xue et al identified Ruminococcus callidus and Lactobacillus gasseri (both belonging to the Firmicutes phylum) as the most significantly associated with AMD after combining data from two population cohorts (Chinese and Swiss) [65], while Zinkernagel et al showed an increase in Oscillibacter, Anaerotruncus, Eubacterium ventriosum, and Ruminococcus torques in AMD patients versus control subjects that, instead, presented a higher content of Bacteroides eggerthii [49]. Still, a reduced Firmicutes/Bacteroides ratio seems to characterize AMD across the different studies [63,65].…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%
“…Moreover, Xue et al identified Ruminococcus callidus and Lactobacillus gasseri (both belonging to the Firmicutes phylum) as the most significantly associated with AMD after combining data from two population cohorts (Chinese and Swiss) [65], while Zinkernagel et al showed an increase in Oscillibacter, Anaerotruncus, Eubacterium ventriosum, and Ruminococcus torques in AMD patients versus control subjects that, instead, presented a higher content of Bacteroides eggerthii [49]. Still, a reduced Firmicutes/Bacteroides ratio seems to characterize AMD across the different studies [63,65]. Metabolically, glutamate degradation, arginine synthesis, and L-alanine fermentation are upregulated in the intestinal microbes from AMD patients [49].…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%
“…Given these constraints, we recommend that future research incorporate more comprehensive approaches alongside the 16S V3-V4 sequencing, such as shotgun metagenomic sequencing. Using a more expansive method will allow for a deeper exploration of the microbiome at the species level and enhance understanding of microbial functionalities [ 49 ]. In addition the administration of antibiotics exerts a significant and lasting impact on the microbiome, with notable alterations in its composition and potentially its operations.…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation was observed between the relative abundance of Clostridials and Firmicutes unknown species-level genome bins and lesion size, central pit thickness, hemorrhage size, and angiographic leakage. In contrast, a negative correlation was observed between lesion and hemorrhage size and the relative abundance of Bacteroidales ( Xue et al, 2023 ).…”
Section: Gm Composition and Metabolites Influence Amd Developmentmentioning
confidence: 90%
“…The occurrence and progression of AMD are linked to abnormal alterations in the GM composition. Although the relationship is unclear, GM dysregulation may play a role in AMD progression by enhancing the signaling pathway to activate the complement system abnormally ( Xue et al, 2023 ). When the complement system is over-activated or dysregulated, the out-of-control complement system becomes a key link in triggering infection and inflammation.…”
Section: Gm Composition and Metabolites Influence Amd Developmentmentioning
confidence: 99%